Sag and Tension of 275 kV Transmission Line using Catenary - Novriandi, Dicky; Zakri, Azriyenni Azhari; Ervianto, Edy (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2019)
This research will develop a catenary method to determine the sag and tension analysis on the 275 kV transmission line conductors. The catenary method is dependent on the equation of the weight of the conductor, the maximum tensile stress of the conducting wire, the length of the span, and the maximum sag of the conductor. The method will be used in determining the value of sag and tension with the design of the model using software AutoCAD. The results of research for the same tower sag height of 6.86 m, with a tension of 4610.83 kg and a conductor length of 401.06 m, while sag for the tower is not the same height of 8.14 m, with a tension of 4612.84 kg, and changes in conductor length 401.06 m. The increase in current causes the sag value to increase, when the minimum current sag value is 6.9828 m, and the maximum current sag value increases to 8.44 m. While the tension will decrease along so that temperature is increased the current minimum pressure of 4531.27kg, and at the time of maximum tension of 3749.728kg. Sag and tension are also affected by ambient temperature when the minimum temperature is 20 ℃ sags are 6.8621 m and when the maximum temperature is 40 ℃ sag increases to 7.793492 m. Tension will decrease with each increase in temperature when the minimum temperature is 20 ℃ tension 4610.538 kg when the maximum temperature is 40 ℃ the tension is reduced to 4062.345 kg.